Chinche Navarrete,Silvana Isabel(2023)Metodología para conservar la viabilidad de las semillas de Tabebuia rosea (Bertol.) BERTERO EX A.DC, en el cantón Quevedo 2022.Quevedo.UTEQ.95p. - Chinche Navarrete, Silvana Isabel (2023)
In important forest species, a loss of seed viability has been identified, which is why strategies should be considered to ensure seed quality and the perpetuation of the species. The objective of this research was to establish the optimal conditions for the storage of Tabebuia rosea seeds. The collection of fruits was carried out from sixteen trees according to the norms of the "International Seed Testing Association (ISTA)". Based on this protocol, viability and germination tests of the samples were evaluated in two germination methods: in vivo (greenhouse) and in vitro (laboratory). A completely randomized design with two factors and an equal number of observations was used to determine the optimum temperature and moisture content for storing the samples for three months. The best results that recorded a high germination percentage were T7 (95,56%) and T8 (96%), through staining with the tetrazolium test did not present significant differences compared to the viability percentage. Tabebuia rosea seeds can be stored with a CH no higher than 5% and low temperatures of 5°C and -10°C as they allowed better preservation of viability due to the decrease in metabolic activity during storage. Ensuring the quality of the seed will depend on the handling, processing and storage conditions that will be established according to the type of seed to be evaluated in order to guarantee viable potential.